Manajemen Pendidikan Berbasis Sistem Penjaminan Mutu Internal di SMK Negeri 9 Samarinda: Diseminasi dan PkM - Zaenab Hanim; Syafrudin Januar; Lukman Priyandono; Soerjo Adi Poernomo; Theresia Ping; Heriman; Rohana Rohana (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Service activity aims to provide education quality assurance assistance following an enhanced digital-based quality assurance cycle to ensure its implementation and supported by the dissemination of relevant research results so that it can run continuously and sustainably to build a school supervision system. This dissemination and community service activity begins with mapping quality based on National Education Standards, making School Work Plans, fulfilling good quality in processing standards in the learning process, monitoring and evaluating implementation, setting new standards, evaluating implementation results, and making a quality assurance system. digital school. This activity produces outputs in the form of a quality-based education management system that includes quality standards, standard operating procedures, curriculum, student data, teachers, student achievements, and teacher achievements.